Comparative efficacy and safety of the artemisinin derivatives compared to quinine for treating severe malaria in children and adults: a systematic update of literature and network meta-analysis - Nyaaba, N; Andoh, NE; Amoh, G; Amuzu, DSY; Ansong, M; Ordóñez-Mena, JM; Hirst, J (Public Library of Science, 2022)
Background The artemisinin derivatives are the preferred antimalaria drugs for treating severe Plasmodium falciparum malaria. However, their clinical effectiveness compared to each other is unknown. Our objective, therefore, was to evaluate the efficacy and safety of the artemisinin derivatives and quinine for treating severe P. falciparum malaria in children and adults using a network meta-analysis.